(untitled) (Bangladesh Journal of Zoology, 2015)
Efficacy of different fertilizers on the growth and survival of brackishwater catfish, Mystus gulio (Hamilton) fry in nursery ponds has been evaluated with three fertilizer treatments (T) viz., T1 - only organic (cattle dung @ 5 tons/ha), T2 - only inorganic (urea @ 50 kg/ha + TSP @ 60 kg/ha) and T3 - mixture of organic + inorganic (cattle dung @ 2.5 tons/ha + urea @ 25 kg/ha +TSP @ 30 kg/ha). After four weeks rearing, survival of fry was highest (69.35 ± 8.79%) in T1 which was significantly higher than those of T2 (46.01 ± 4.17%) and T3 (57.19 ± 6.22). But no significant difference in final length (2.70 - 2.79cm) and final weight (0.83 - 0.93 g) among three treatments was observed. Physicochemical variables of water and planktons of different treatments were recorded and discussed. Bangladesh J. Zool. 41(1): 21-27, 2013